Síndrome metabólica e seus componetes e a densidade mineral óssea de adolescentes com excesso de peso - Silva, Valéria Nóbrega da [UNESP] (2014)
Objective: To evaluate the influence of MS and each component on bone mineral density of the lumbar spine, total proximal femur and both total body subtotal of overweight adolescents. Subjects and Methods This is a cross-sectional study with 271 overweight, obese and extremely obese adolescents (aged 10 to 16 years). Anthropometric and biochemical tests were performed. The BMD of the lumbar spine, proximal femur, and both total and subtotal body were obtained via bone densitometry through dual energy x-ray absorptiometry (DXA) and transformed BMD kg weight (g/cm²/kg weight). MS was defined according to the criteria for children and adolescents proposed by the International Diabetes Federation. Results Out of 271 adolescents, 39 were positive for MS (14%). Overweight adolescents that were positive for MS presented a significant decrease in BMD (g/cm²/kg body weight) in all sites that were evaluated (p<0.01). Female adolescents with big waist circumference, low HDLc, hypertriglyceridemia and presence of high arterial blood pressure displayed significant diminishment in BMD in all sites that were evaluated (p<0.01), which was also observed for male adolescents, except for the increased triglycerides which had no effect on BMD (p>0.05). Through linear regression analysis, it was observed that waist circumference was negatively correlated with BMD for both genders and triglycerides were only negatively correlated with BMD for female adolescents. Conclusion Our results suggest that overweight adolescents that present MS display lower bone mass. From all MS components, waist circumference was a major determinant factor for the reduction of BMD